Density dependence and cooperation: theory and a test with bacteria. - Ross-Gillespie, A; Gardner, A; Buckling, A; West, SA; Griffin, A (2009)
Although cooperative systems can persist in nature despite the potential for exploitation by noncooperators, it is often observed that small changes in population demography can tip the balance of selective forces for or against cooperation. Here we consider the role of population density in the context of microbial cooperation. First, we account for conflicting results from recent studies by demonstrating theoretically that: (1) for public goods cooperation, higher densities are relatively unfavorable for cooperation; (2) in contrast, for self-restraint-type cooperation, higher densities can be either favorable or unfavorable for cooperation, depending on the details of the system. We then test our predictions concerning public goods cooperation using strains of the pathogenic bacterium Pseudomonas aeruginosa that produce variable levels of a public good-iron-scavenging siderophore molecules. As predicted, we found that the relative fitness of cheats (under-producers) was greatest at higher population densities. Furthermore, as assumed by theory, we show that this occurs because cheats are better able to exploit the cooperative siderophore production of other cells when they are physically closer to them.